THE EFFECT OF BAY LEAF GARLIC DECOCTIONON ON LOW CHOLINESTERASE LEVELS DUE TO PESTICIDE EXPOSURE IN FARMERS IN PASURUAN - Mukhammad Toha; Ida Zuhroidah; Mokh Sujarwadi (Institute for Research and Community Service of Health Polytechnic of Kerta Cendekia, Sidoarjo, 2023)
Background: Pesticides are chemicals used by farmers to control and kill pests and diseases. Pesticides can poison humans, although their main use is to control and kill agricultural pests. Pesticide poisoning is still a problem that often occurs in society. Objectives: The aim of this study was to determine the effectiveness of garlic and bay leaf decoction in increasing cholinesterase levels of farmers exposed to pesticides in Pasuruan Raya. Methods: The design of this study was a pre-experimental, one-group pretest-posttest with a population of rice processing farmers in Pasuruan Raya. The sample size used was 20 farmers taken by purposive sampling. The independent variable was the administration of a decoction of garlic and bay leaf for fifteen days, the dependent variable was the level of cholinesterase in the blood. Data were analyzed using paired sample t test. Conclusion: The use of garlic and bay leaf decoction in this study is a complementary therapy given to farmers as a regulator of reducing cholinesterase levels which is an indicator of the accumulation of pesticides in the body. It is expected to be an effective and efficient solution. it is hoped that farmers will be able to independently maintain their health through smart techniques in utilizing local wisdom resources by cultivating materials, managing, preparing and processing natural materials into medicines that can be done independently, not only able to improve health status but also provide opportunities for development into business ventures creative economy that can increase income and economic welfare.